Active and Semi Active Vibration Isolation Systems Based on Magnetorheological Materials. (2015) - Bazinenkov, Alexey M.; Mikhailov, Valery P.
Abstract: The paper presents active vibration isolation systems based on "smart" materials. Very promising "smart" materials are MR elastomers. Devices based on them have the ability to work in all vibration isolation modes (passive, semi-active and active mode). In this work we consider a construction of a damper based on the MR elastomer and the experimental research results of the damper in semi-active vibration isolation mode.